PENGARUH MODEL PEMBELAJARAN BAMBOO DANCING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DI KELAS VIII MTS AL-ITTIHADIYAH MEDAN - Ghina Fathirah Pasaribu; Isran Rasyid Karo Karo S (State Islamic University of North Sumatra, 2019)
This study was aimed to determine the effect of Bamboo Dancing learning models on mathematical communication skills of students in class VIII of MTs Al-Ittihadiyah Medan. This research was a quantitative research, with a type of quasi-experimental research. The population was all students of class VIII MTs Al-Ittihadiyah Medan 2016/2017 Academic Year. The sample of this study was students of class VIII-4, which amounted to 26 people as the experimental class, and students of class VIII-5 which amounted to 26 people as the control class. From the analysis of the data obtained findings that there are differences in the mathematical communication skills of students in the experimental class using Bamboo Dancing learning models and control classes that use conventional learning. The average value of the experimental class for the initial test (pre-test) was 43.85 with a standard deviation of 9.20, while the average value for the final test (post-test) was 81.54 with a standard deviation of 9.98. In the control class the average value obtained for the initial test (pre-test) was 48.08 with a standard deviation of 10.01, whereas for the final test score (post-test) was 75.38 with a standard deviation of 13,11. In hypothesis testing using the t-test with sig. , obtained by t = 2.011, and t table = 2.009, thus obtained t t tabel atau 2,011 t table or 2.011 2,009, so that Ha is accepted, namely there is a significant influence between the Bamboo Dancing learning model on the mathematical communication skills of students in class VIII of MTs Al-Ittihadiyah Medan.